Test-retest reliability of an Android application (Protractor) for range of motion evaluation - Mohamed Elkady, Sabah; Abd Elrazik, Reda Kotb; Mohammed Alsaid, Hossam; Youssef Elhamrawy, Mohammed; Mashaal, Ahmed; Mohamed Abdel Wahid, Amany Refaat; Atef, Doaa (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Several tools are used by physical therapists to assess the range of motion (ROM) for joints of the upper and lower limbs. However, most of them are costly, time-consuming, and difficult to use. The current study aimed to determine the within-visit test-retest reliability of an android application (App) (Protractor) for elbow, wrist and ankle joints range of motion evaluation in outpatients with post fracture fixation. We evaluated the Android App (Protractor) in twenty-six patients with a mean age of 30 years, who had undergone operative treatment for fractures around the elbow, wrist, and ankle. These patients were recruited from the physiotherapy outpatient clinic at the Faculty of Medicine, Tanta University. Repeated measures were performed within the same session, focusing on motions in the sagittal plane for the elbow, wrist, and ankle joints. All measurements were conducted by the same investigator. Pearson correlation coefficient (r) and intra-class correlation coefficient (ICC) were calculated. Within-visit test retest intra-rater reliability for elbow, ankle, and wrist joints, ROM was excellent (r and ICC≥0.99) except for wrist joint flexion ROM, it was weak and insignificant. The mean group difference of measures obtained in the first and second measurements was close to zero, with the exception of wrist joint flexion, which was -5 degrees, and ankle joint plantar flexion, which was +2 degrees. The Smartphone android App (Protractor) displayed reasonable within-visit reliability.